HONEY, MORE THAN JUST FOOD: THE POSSIBILITY OF APPLICATION IN REGENERATIVE MEDICINE - Živković, Jelena; Najdanović, Jelena (Acta medicae Medianae, 2022)
Honey has long been recognized as a special natural product, not only because of its nutritional value, but also because of its healing properties. Although it is mostly composed of carbohydrates, it also contains numerous enzymes, amino acids, organic acids, polyphenols, minerals, vitamins and other substances, whose presence varies depending on the type of honey and its botanical and geographical origin. Thanks to its antimicrobial properties, as well as its beneficial effect on wound healing, tissue repair and regeneration, honey could have a potential role in the fields of tissue engineering and regenerative medicine.